An analysis of teacher feedback on seventh grade students’ English homework at SMPN 1 Kota Solok - Dini, Vioren; Syafei, An Fauzia Rozani (Universitas Negeri Padang, 2025)
Feedback is a crucial component in language learning as it guides students to identify their strengths and weaknesses. This study aims to analyse the types and forms of teacher feedback on seventh-grade students’ English homework at SMPN 1 Kota Solok, as well as the teachers’ purposes and considerations in providing such feedback. This research employed a qualitative descriptive design. The data were obtained through document analysis of students’ English homework and interviews with three English teachers. The findings revealed that evaluative feedback was the most dominant type (83.05%), followed by motivational feedback (14.41%) and corrective feedback (2.54%), while formative, advisory, praise, and criticism feedback were not found. In terms of form, symbolic or code feedback was most frequently used (83.05%), followed by general feedback (16.95%), with no written feedback identified. The interview results showed that teachers emphasized clarity, motivation, and balance between correction and encouragement, but inconsistently monitored students’ progress and guided improvement. Overall, the study concludes that teacher feedback practices remain heavily evaluative and limited in formative aspects. Therefore, teachers are encouraged to provide more constructive, descriptive, and formative feedback to help students understand their errors, promote engagement, and improve their English learning outcomes.